Nitrogen and phosphorus uptake kinetics in cultures of two novel picoplankton groups responsible for a recent bloom event in a subtropical estuary (Indian River Lagoon, Florida) - Papacek, Joshua R.; Inglett, Patrick W.; Phlips, Edward J.; Lasi, Margaret A. (Frontiers in Marine Science, 2024)
Introduction Successful management and mitigation of harmful algal blooms (HABs) requires an in-depth understanding of the physiology and nutrient utilization of the organisms responsible. We explored the preference of various nitrogen (N) and phosphorus (P) substrates by two novel groups of HAB-forming phytoplankton originating from the Indian River Lagoon (IRL), Florida: 1) a consortium of picocyanobacteria (Crocosphaera sp. and ‘Synechococcus’ sp.) and 2) ananochlorophyte (Picochlorum sp.). Methods Short-term kinetic uptake experiments tested algal use and affinity for inorganic and organic N substrates (ammonium (NH4+), nitrate (NO3-), urea, and an amino acid (AA) mixture) through 15N and 13C isotope tracing into biomass. Results Picocyanobacteria exhibited Michaelis-Menten type uptake for the AA mixture only, while nanochlorophytes reached saturation for NH4+, the AA mixture, and urea at or below 25 µM-N. Both picocyanobacteria and nanochlorophyte cultures had highest affinity (Vmax/Ks) for NH4+ followed by the AA mixture and urea. Neither culture showed significant uptake of isotopically-labeled nitrate. Disappearance of glucose-6-phosphate (G6P) added to culture medium suggesting use of organic P by both cultures was confirmed by detection of alkaline phosphatase activity and the tracing of 13C-G6P into biomass. Discussion Together, our results suggest that these HAB-forming phytoplankton groups are able to use a variety of N and P sources including organic forms, and prefer reduced forms of N. These traits are likely favorable under conditions found in the IRL during periods of significant competition for low concentrations of inorganic nutrients. Bloom-forming phytoplankton are therefore able to subsist on organic or recycled forms of N and P that typically dominate the IRL nutrient pools.